THE EFFECT OF EDUCATION, TRAINING AND MOTIVATION ON PERFORMANCE THROUGH COMPETENCE IN MEMBERS OF THE DIRECTORATE OF DRUG INVESTIGATION OF THE RIAU ISLANDS REGIONAL POLICE - Lorehan Septiadi, Dewo; Wibisono, Chabullah; Catra Asa, I Wayan; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study is to determine and analyze the effect of education, training and motivation on performance through competence in members of the Directorate of Drug Investigations of the Riau Islands Regional Police. The method used in this study was a causal model survey method, data collection using questionnaires and distributed to 118 respondents. Statistical data analysis using SEM-PLS (Sructural Equation Modelling- Partial east Square) and using path analysis to test relationship patterns that reveal the influence of variables on other variables, both direct and indirect influences assisted by Smart PLS Ver 4.0 software. The results in the study showed that education directly has a positive and significant effect on employee competence with a p-value of 0.000 < 0.05, training directly has a positive and significant effect on competence with a p-value of 0.000< 0.05, competence directly affects positive and significant performance with a p-value of 0.002 < 0.05, education directly affects positive and significant performance with p-value of 0.316 < 0.05, training directly has a positive and significant effect on performance with a p-value of 0.562 < 0.05, motivation directly affects performance with a p-value of 0.000 < 0.05, performance directly affects positive and significant through educational mediation on employee kineja with a p-value of 0.000 < 0.05, performance of positive and significant influence through mediation of training media on competence with p-value 0.019 < 0.05, positive and non-signific influence performance through motivational mediation on competence with p-value 0.03326 <0.05.